Can the Anesthesiologist Use the Radial Artery for Monitoring After Transradial Artery Catheterization?. (15th June 2015) - Awad, Hamdy; Quevedo, Eduardo; Abas, Motaz; Brown, Michelle; Satiani, Bhagwan; Capers, Quinn; Starr, Jean E.
Abstract : The use of transradial coronary angiography and intervention is growing because of its advantages over the femoral approach. However, the small size of the radial artery can contribute to complications. We present a case of an in situ access complication of transradial coronary artery catheterization. It is important for the anesthesiologist to know about the short-term and long-term consequences of this intervention, which could lead to narrowing of the artery even beyond the site of puncture. Understanding these changes could help anesthesiologists make better decisions about using the radial artery for monitoring after transradial coronary artery catheterization procedures.